Pemanfaatan Teknologi Informasi dalam Pemberdayaan Peningkatan Sumber Daya UMKM di Kelurahan Mangolo Kecamatan Latambaga Kabupaten Kolaka - Irawati; Sulfikar Sallu; Rabiah Adawiyah; Noorhasanah (Indonesian Journal of Community Services, 2022)
Information technology socialization to micro business actors is needed to improve their knowledge in the field of Information Technology and especially to expand their reach marketing and create other business opportunities that are in line with existing businesses. Technology models that socialize and make the training usable to market the products to be offered. Implementation of devotion This community is targeted at Micro or home-based business actors whose business locations are in the region Mango Village, Kolaka Subdistrict, Kolaka Regency. The purpose of this service is that participants in the socialization and training can apply the knowledge gained to increase the marketability of their products outside the current location of the production area so that business competitiveness can be improved. The socialization material provided is how to optimize the use of mobile devices and determine mobile applications and create websites that are in accordance with the products sold so that their products can be marketed at national and international levels.